Data Mining Penjualan Produk dengan Algoritma Apriori Pada Jims Honey Pangkalpinang - Parlia Romadiana; Delpiah Wahyuningsih; Cindy Aprilia; Amanda Monica; A Anisah; Syafrul Irawadi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Jims honey is a product that is in great demand by all groups and is a current fashion trend, especially among teenagers and mothers. At Jims honey Pangkalpinang, which is located on Jl Darul Mahabbah, sales are currently very rapid, especially when sales are made online. At this time Jims Honey has become a lot of resellers in every district on Bangka Island. Sales in one month sold more than 1,000 products from a variety of Jims Honey products. The purpose of this research is to find out which products are the most selling to the lowest each month with the a priori algorithm. Where the stage of this research method is carried out first to obtain overall data for that month. The second stage is analysis using the apriodi algorithm, the third stage is applying the a priori algorithm system with data mining obtained at Jims Honey Pangkalpinang to find the best-selling to lowest data product results for that month.